Investigating Students’ Intrinsic Motivation and Engagement in Developing Integrated English Language Skill: Efl Instruction at Kadamjay Semetey High School - Milla Quaidy, Gusti; Goqid Bashar, Rivano; Ernest, Isakov; Abdurrahman, Kalambekov; Khairani, Zamratul (BiCED Proceeding, 2023)
The acquisition of four essential English language skills, namely listening, speaking, reading, and writing, necessitates active practice and usage. However, learners often encounter challenges in utilizing these skills due to various constraints, such as limited access to opportunities for English language use. Consequently, learners may struggle to achieve their English language learning goals. To create an optimal learning environment for English language acquisition, educators are expected to incorporate all four language skills into the instructional process, thereby providing students with a supportive context for skill development. This research investigates the integration of the four English language skills within the classroom learning process and explores students' perspectives on the realization of these skills. Employing a qualitative research approach, this study utilizes interviews as the primary research instrument.